Pengaruh Pendekatan Matematika Realistik Terhadap Kemampuan Literasi Matematika Siswa Kelas III SD Negeri 0406 Aek Tinga - Windy Meilani Lubis (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
The use of a mathematics learning approach is still not fully used optimally. The purpose of this study was to determine the use and effect of a realistic mathematical approach on the mathematical literacy skills of third grade students at SD Negeri 0406 Aek Tinga. The type of research used is experimental research of the One Group Pretest-Ptostes Design type. Data collection techniques used are written test instruments, and observation sheets. With 24 class III students of SD Negeri 0406 Aek Tinga as the research sample. Based on the research that has been done, there is an effect of a realistic mathematical approach on the mathematical literacy skills of third grade students at SD Negeri 0406 Aek Tinga. This is proven through the results of hypothesis testing using the t test showing that the value of tcount = 5,481, with a level of a = 0,05 with degrees of freedom (df) 24-1 = 23, the results obtained ttable = 2,0687. The calculation results obtained tcount > ttable = 5,481 > 2,0687. Thus it can be concluded that the realistic mathematical approach has an effect on the mathematical literacy abilities of class III students at SD Negeri 0406 Aek Tinga. Based on the results of the research, it is better if the realistic mathematical approach can be used optimally.